Motivation mediating effect on principals’ personality, job satisfaction, and affective commitment - Adisel Adisel; Hegar Harini; Ahmad Gawdy Prananosa; Onsardi Onsardi; Sulistianingsih Sulistianingsih; Robeet Thadi (Institute of Advanced Engineering and Science, 2024)
Affective commitment is ultimately carried out by a leader in an organization, including in high schools. This study mainly aims to examine the influence of personality and job satisfaction on the affective commitment of high school principals mediated by motivation. A quantitative survey was employed in this study. The sample studied was 90 public high school principals in Jakarta, Indonesia. The data were collected through a questionnaire, which has been tested for validity and reliability. The data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) using SmartPLS 3.0 software. The results showed a significant relationship between the public school principals’ personality and job satisfaction on their affective commitment which is mediated by motivation. In more detail, the results indicated: i) a positive direct effect of personality on affective commitment, personality on motivation, and job satisfaction on the motivation of public school principals; ii) no significant direct effect of job satisfaction on affective commitment; and iii) a mediating role of motivation, that directs to a positive and significant influence on personality, job satisfaction, and principals’ affective commitment. The study’s implications for related authorities are presented.